2018
DOI: 10.1021/acs.jpclett.8b02325
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Vibronic-Coupling-Mediated Energy Transfer in Light-Harvesting Nanotubes Stabilized in a Solid-State Matrix

Abstract: Ultrafast vibrational spectroscopy is employed to obtain real-time structural information on energy transport in double-walled light-harvesting nanotubes at room temperature, stabilized in a host matrix to mimic the rigid scaffolds of natural light-harvesting systems. We observe evidence of a low-frequency vibrational mode at 315 cm, which transfers excitons from the outer wall of the nanotubes to a crossing point through which energy transfer to the inner wall can occur. This mode is furthermore absent in sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 55 publications
(108 reference statements)
7
27
0
Order By: Relevance
“…The transfer rate from the outer to the inner tube was measured using conventional 2D spectroscopy (Supplementary Note 13 and Supplementary Fig. 24) and agrees with the values from literature 18,69,70 . The opposite rate (inner → outer) follows from the condition that the inner and outer tube exciton populations eventually reach thermal equilibrium, where the net inter-tube transfer rates are identical 63,64 .…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…The transfer rate from the outer to the inner tube was measured using conventional 2D spectroscopy (Supplementary Note 13 and Supplementary Fig. 24) and agrees with the values from literature 18,69,70 . The opposite rate (inner → outer) follows from the condition that the inner and outer tube exciton populations eventually reach thermal equilibrium, where the net inter-tube transfer rates are identical 63,64 .…”
Section: Methodssupporting
confidence: 82%
“…Recent studies have focused on reducing the complexity of multi-layered, supramolecular nanotubes and thereby essentially uncoupling individual hierarchical units, i.e., the inner and outer layer of the assembly by oxidation chemistry 7,8,17,18 . In addition, Eisele et al have demonstrated flash-dilution as an elegant tool to selectively dissolve the outer layer to obtain an unobscured view on the isolated inner layer 7,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Elsewhere, the rigid scaffold chromophore interactions of natural lightharvesting systems have been mimicked with cyanine dye-derived host solid-state matrix. Focusing on the structural similarities to chromosomal assemblies in green sulfur bacteria capable of low-light photosynthesis, the solid-state environment was found to modulate vibronic coupling of the system and direct energy transfer [192]. Agglomeration of dyes into nanotubes and structured bundles bio-inspired green bacteria facilitated longer exciton diffusion lengths and wider exciton delocalisation consistent with theory [193][194][195].…”
Section: Bio-inspired Synthetic Light Harvesting Systemsmentioning
confidence: 66%
“…We prepare the stabilized aggregates using a previously reported sugar matrix stabilization procedure (pictures shown in Figure 3c). 39,52 Comparison of solution and sugar matrix stabilized aggregates (shown in SI Figure S8a) strongly suggests that the aggregate morphology remains intact in sugar matrix. Upon cooling down from room temperature to 78 K, we find that the full-width at half-maximum (FWHM) of Cy7-DPA peak narrows from 463 cm -1 to 303 cm -1 (34 %) and red shifts by 150 cm -1 as shown in Figures 3d-e.…”
Section: Resultsmentioning
confidence: 95%